Comparative study in prolapse lumbar intervertebral disc (PLID) surgery by spinal vs general anaesthesia - Chowdhury, Md Shahnewaz; Roy, Sabya Sachi; Rahman, Md Matiur; Hossain, Md Mozaffer; Alim, SMA (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background Lumbar discectomy is most commonly performed under general anaesthesia, which can be associated with several perioperative morbidities including nausea, vomiting, atelectasis, pulmonary aspiration, and prolonged post-anaesthesia recovery. It is possible that fewer complications may occur if the procedure is performed under spinal anesthesia. Objective We have compared patient satisfaction between spinal versus general anaesthesia in patients for single level lumbar surgery. Methods Eighty consecutive patients of ASA grade I-II were recruited and randomized into two equal groups, with half of this patients receiving spinal anaesthesia (n-40) and the remainder general anaesthesia (n-40). A comprehensive postoperative evaluation was carried out documenting any anaesthetic complications, pace of physiological and functional recovery and patient satisfaction. Variables were recorded as pain level using a visual analogue scale (VAS) at 1, 6, 12 and 24 hours; patient level of satisfaction during the stay on the ward using verbal rating scale (VRS) as it was detected by A p-value < 0.05 were considered as significant. Results Spinal anaesthesia patients achieved the milestones of physiological and functional recovery more rapidly and reported less postoperative pain. Perioperative hypotension in 25 % of patients and none was hypertensive in spinal group and in G/A Group 05% of patients was hypotensive and 20% were hypertensive. Postoperative pain intensity more in G/A group than spinal group. Patient satisfaction in spinal group was more comparative to G/A group. Conclusion Spinal anaesthesia ensures better operating conditions, better postoperative pain control and a quicker postoperative recovery when compared to general anaesthesia for single level lumbar spine surgery DOI: http://dx.doi.org/10.3329/jbsa.v23i2.18173 Journal of BSA, 2009; 23(2): 47-50